Family adoption programme implementation feedback from undergraduate medical students in Almora: A cross-sectional study - Preeti; Thakkar Hemaben Kanubhai; Vikram Singh Dhapola (Journal of Family Medicine and Primary Care)
Background: The Family Adoption Programme (FAP) aims to provide a learning opportunity to Indian medical graduates towards community-based health care. This study describes the perspective of medical undergraduate students towards the FAP implementation at the government medical college in Almora. Methods: An observational study was conducted on the students of phases I and II in the government medical college, Almora, on the hurdles and facilitators of FAP via Google Form. Out of 199 students, 193 filled out the form, which was eligible for evaluation. A brief orientation was conducted on the FAP as recommended by the National Medical Commission of India, which was followed by sensitization of the students to the FAP proforma. Periodic FAP visits were planned for students along with their assigned mentors at the selected nearby three villages. During these visits, students interacted with the families, and details regarding the health profile of the family were documented. Students wrote reflections on FAP visits in the log book which were reviewed by faculties. Gibbs reflective cycle was also applied among the students who were allotted families for better understanding. Results: A total of 199 students were enrolled in FAP, and out of those, 193 submitted feedback through a Google link. Overall, the experience was graded as good (53.6%), while 35.4% responded that it was excellent. Conclusion: Better implementation of FAP needs planning, intersectoral co-ordination, good sensitisation, and training activities for field staff, faculty and the community.